2020
DOI: 10.1002/cbdv.202000490
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibitory Carbazole Alkaloids from the Folk Medicine Murraya tetramera C.C. Huang

Abstract: The phytochemical investigation of the leaves and stems of Murraya tetramera C.C. Huang, a traditional folk medicine used as an anti-inflammatory agent, yielded 19 simple carbazole alkaloids, two of which (1-ethoxy-3methyl-9H-carbazol-2-ol (1) and 7-hydroxy-2,8-dimethoxy-6-methyl-9H-carbazole-1-carbaldehyde (2)) are new ones. The structures of the new compounds were determined by extensive spectroscopic analysis including NMR and HR-EI-MS experiments, as well as comparison with the reported data. Most of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Microphyltrine, microphyldines A-O and microphyldine P were isolated from the stem and leaves of M. microphylla [41]. Nitric oxide production induced by LPS in BV-2 microglial cells was inhibited by phyto-carbazole alkaloids from M. tetramera and M. kwangsiensis [19,42], with IC 50 values ranging from 5.1 to 15.1 µM [43].…”
Section: Phyto-carbazole Alkaloids From the Genus Murrayamentioning
confidence: 99%
“…Microphyltrine, microphyldines A-O and microphyldine P were isolated from the stem and leaves of M. microphylla [41]. Nitric oxide production induced by LPS in BV-2 microglial cells was inhibited by phyto-carbazole alkaloids from M. tetramera and M. kwangsiensis [19,42], with IC 50 values ranging from 5.1 to 15.1 µM [43].…”
Section: Phyto-carbazole Alkaloids From the Genus Murrayamentioning
confidence: 99%
“…With the application and development of detection technology, the effective components with medicinal value have been gradually isolated and identified. In vitro activity studies have shown that the flavonoids and alkaloids of M. tetramera have significant inhibitory effects on many cancer cells [12,13], as well as anti-inflammatory and analgesic effects [14,15]and anthelmintic effects [16]. Alkaloids are intermediates of plant nitrogen metabolism derived from different amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16]. M. tetramera contains various flavonoids, coumarins, alkaloids, and sesquiterpenes [17][18][19][20]. Some of the isolated compounds have exhibited significant cytotoxic effects [20][21][22].…”
Section: Introductionmentioning
confidence: 99%